Cell motility and biofilm formation in Bacillus subtilis are affected by the ribosomal proteins, S11 and S21. Issue 5 (4th May 2014) - Takada, Hiraku; Morita, Masato; Shiwa, Yuh; Sugimoto, Ryoma; Suzuki, Shota; Kawamura, Fujio; Yoshikawa, Hirofumi
Abstract: Bacillus subtilis differentiates into various cellular states in response to environmental changes. It exists in two states during the exponential growth phase: motile cells and connected chains of sessile cells. Here, we identified new regulators of cell motility and chaining, the ribosomal proteins S21 ( rpsU ) and S11 ( rpsK ). Their mutants showed impaired cell motility (observed in a laboratory strain) and robust biofilm formation (observed in an undomesticated strain). The two major operons for biofilm formation, tapA - sipW - tasA and epsA - O, were strongly expressed in the rpsU mutant, whereas the flagellin-encoding hag gene and other SigD-dependent motility regulons were not. Genetic analysis revealed that the mutation of remA, the transcriptional activator of the eps operon, is epistatic to that of rpsU, whereas the mutation of antagonistic regulators of SinR is not. Our studies demonstrate that S11 and S21 participate in the regulation of bistability via the RemA/RemB pathway. Graphical abstract: : rpsU, encoding ribosomal protein S21, mutant strains showed cell separation and swimming defects due to the inactivation of SigD.